Depression and coping strategies among sexually abused children : a preliminary study - Yusoff, Rosliwati Md (2006)
Background: Child sexual abuse is a complex life experience and it is associated with depression. Sexually abused children cope with the experiences differently. Depression is a major mental health concern worldwide. There is no previous local study on screening for depression and coping strategies used in child sexual abuse in Malaysia. Objectives: This study aimed to describe the psychosocial factors and coping strategies used and its association with depression in sexually abused children. Methods: The study consisted of 2 stages. First, the validation of the Malay version of COl and followed by a cross sectional study of depression and coping strategies used, participated by 65 sexually abused children and adolescents attending HUSM. The following measures were used: general questionnaire, semi-structured questionnaire of coping strategies and the validated Malay version-COl. Depression was defined as score above the optimum cut-off point on Malay version-COl determined at the validation study. Results: The validation study showed that at the cut-off score of 18, the COl had 90% sensitivity and 98% specificity in detecting depression. In the study sample, 16 (24.6%) participants had been depressed and 49 (75.4%) participants had not been depressed. In coping strategies, 57 (87.7%) used emotion-focused coping strategies, 6 (9.2%) used problem or task-focused coping strategies and 2 (3.1 %) used both emotion and problem-focused. Among emotion-focused coping strategies, participants used (i) deciding than nothing can be done to change things, (ii) denial and (iii) suppression. Conclusion: The screening of depression in the vulnerable group such as child sexual abuse was important, as for early detection and treatment. By recognizing the coping strategies used in sexually abused children, it can be helpful for clinician and counselor in their counseling session.